KENDALA MAHASISWA BARU TERHADAP PEMBELAJARAN DARING DAN SOLUSINYA DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Mohammad Jailani; Dea Aprilia (PENAIS (Jurnal Pendidikan Agama Islam), 2023)
Online learning is now an alternative learning that is applied to facilitate communication of material delivery in distances. The purpose of this study is to explain what obstacles new students experience on several campuses when participating in online learning along with solutions that can be applied. This type of research is qualitative descriptive research. The subjects of this study are new students on various campuses with different study programs. The research data was collected using the questionnaire method from Google Form with 5 respondents. In Islam as a Muslim studying is an obligation that must be carried out. The results showed that all of these students had obstacles in carrying out online learning. Therefore, improvements are needed from several aspects so that the vehicle can be minimized. In the time aspect, lecturers are expected to provide time tolerance to students in working on and collecting assignments. In the aspect of providing material, lecturers are expected to provide detailed explanations in videos and voice messages. In the aspect of the method, students prefer a mixed learning method / blanded learning.